Pengaruh Kualitas Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen pada Bagoes Cafe Kota Padang - Fadila Fajriana; Endang Sutrisna (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Competition in the increasingly fierce culinary industry encourages business people to increase competitive advantage. Therefore, this study aims to determine the effect of product quality on consumer loyalty, to determine the effect of product quality on consumer satisfaction, to determine the effect of consumer satisfaction on consumer loyalty, and to determine the effect of product quality on consumer loyalty through consumer satisfaction at Bagoes Cafe Padang City. This research uses quantitative research methods. The sampling technique used was Accidental Sampling with a sample size of 94 people. The results of this study indicate that product quality has a significant effect directly on consumer loyalty, product quality has a significant effect directly on consumer satisfaction, consumer satisfaction has a significant effect directly on consumer loyalty, and product quality has a significant effect indirectly on consumer loyalty through consumer satisfaction.